Detrital apatite fission track analyses of the Subei basin: implications for basin-range structure of the northern Tibetan Plateau. Issue 2 (25th January 2017) - Li, Jianfeng; Zhang, Zhicheng; Zhao, Yue; Pei, Junling; Tang, Wenhao; Li, Ke
ABSTRACT: The northern Tibetan Plateau has evolved a unique basin-range structure characterized by alternating elongated mountain ranges and basins over a history of multiple tectonic and fault activities. The Subei basin recorded evolution of this basin-range structure. In this study, detailed detrital apatite fission track (AFT) thermochronological studies in conjunction with previously documented data reveal provenance of the Subei basin, important information about the Indo-Eurasia collision, and two Miocene uplift and exhumation events of the northern Tibetan Plateau. Detrital AFT analyses combined with sedimentary evidences demonstrate that the Danghenanshan Mountains is the major provenance of the Subei basin. In addition, very old age peaks indicate that part sediments in the Subei basin are recycling sediments. Age peak populations of 70–44 Ma and 61–45 Ma from the lower and upper Baiyanghe formations record the tectono-thermal response to the Indo-Eurasia collision. Combined detrital AFT thermochronology, magnetostratigraphy and petrography results demonstrate the middle Miocene uplift and exhumation event initiated 14–12 Ma in the Subei basin, which may resulted from the Miocene east-west extension of the Tibetan Plateau. Another stronger uplift and exhumation event occurred in the late Miocene resulted from strengthened tectonic movement and climate. A much younger AFT grain age, breccia of diluvial facies and boulders of root fan subfacies record the late Miocene unroofing in the Danghenanshan Mountains.